The effect of tracers' physical properties on retention time measurements inside the conditioner of a pellet mill - Salim, Esam A. (Kansas State University, 2008)
The effect of tracer particle size on the accuracy of measuring retention time inside the conditioner of a pellet mill was studied. Three experiments were conducted using tracers with different particle sizes. The control retention time was calculated using the hold-up capacity method, while retention times for treatments were calculated using the pulse-input method. In addition to the previously prepared tracers, crystalline salt and powder color dye were used as tracers in this study to represent small particle tracers. In experiment one, large, medium, and small tracers were used. The treatment with large particle size was closer to the control with differences around 1.5%. Conversely, using the tracer with small particle size resulted in larger differences, approximately 18%. Two tracers were used in experiment two, resulted in 33% difference between treatment and control using a small particle size tracer, and a 10% difference using a tracer with similar particle size to the main materials. A tracer similar in particle size to the materials flowing inside the conditioner was used in the third experiment in addition to the salt and dye. Statistical analyses for this experiment indicated that particle size affects the accuracy of retention time measurements. There was a significant difference (P<0.05) in the comparison between salt and red color dye in treatment two, while there was no significant difference (P>0.05) between them in treatment one (same particle size). Moreover, in another comparison of the differences between treatments and their related controls, there was significant difference (P<0.05). However, the P-value for the red dye comparison (0.0126) was higher than that of salt (0.0026), which adds density as another influential factor that affects retention time measurement.
Keywords: Retention Time; Pellet Mill; Tracer Particle Size; Tracer Physical Properties; Conditioner; Particle Size; Agriculture, Animal Culture and Nutrition (0475); Agriculture, Food Science and Technology (0359); Agriculture, General (0473)